ON δ-PRIMARY HYPERIDEALS OF COMMUTATIVE SEMIHYPERRINGS - Abumghaiseeb, Ashraf; Ersoy, Bayram Ali (YILDIZ TECHNICAL UNIV, 2018)
In this paper, we study the mapping.. that assigns to each hyperideal I of the commutative semihyperring R, another hyperideal delta(I) of the same semihyperring. Also we introduced the notation of delta-zero divisor of commutative semihyperring and delta-semidomainlike semihyperring which is generalization to those in the semirings. Moreover we showed that if delta be a global hyperideal expansion then I is delta-primary if and only if Z(delta) (R/I) subset of ({0(R/I)}). /})/.
Keywords: Semihyperring; hyperideal; delta-primary; delta-semidomailike semihyperring; Engineering